Modified Linggui Zhugan Decoction protects against ventricular remodeling through ameliorating mitochondrial damage in post-myocardial infarction rats - Xiang, Mi; Zhao, Xin; Lu, Yingdong; Zhang, Yang; Ding, Fan; Lv, Lifei; Wang, Yuling; Shen, Zihuan; Li, Li; Cui, Xiangning (Frontiers in Cardiovascular Medicine, 2023)
Introduction Modified Linggui Zhugan Decoction (MLZD) is a Traditional Chinese Medicine prescription developed from Linggui Zhugan Decoction (LZD) that has been used for the clinical treatment of ischemic cardiovascular diseases. However, the cardioprotective mechanism of MLZD against post-myocardial infarction (MI) ventricular remodeling remains unclear. Methods We explored the effects of MLZD on ventricular remodeling and their underlying mechanisms, respectively, in SD rats with MI models and in H9c2 cardiomyocytes with oxygen-glucose deprivation (OGD) models. The cardiac structure and function of rats were measured by echocardiography, HE staining, and Masson staining. Apoptosis, inflammation, mitochondrial structure and function, and sirtuin 3 (SIRT3) expression were additionally examined. Results MLZD treatment significantly ameliorated cardiac structure and function, and thus reversed ventricular remodeling, compared with the control. Further research showed that MLZD ameliorated mitochondrial structural disruption, protected against mitochondrial dynamics disorder, restored impaired mitochondrial function, inhibited inflammation, and thus inhibited apoptosis. Moreover, the decreased expression level of SIRT3 was enhanced after MLZD treatment. The protective effects of MLZD on SIRT3 and mitochondria, nevertheless, were blocked by 3-TYP, a selective inhibitor of SIRT3. Discussion These findings together revealed that MLZD could improve the ventricular remodeling of MI rats by ameliorating mitochondrial damage and its associated apoptosis, which might exert protective effects by targeting SIRT3.